2021
DOI: 10.1021/acsami.1c05262
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Hierarchical Order and Plasmonic Coupling of Large-Area, Polymer-Grafted Gold Nanorod Assemblies via Flow-Coating

Abstract: Solution-based printing of anisotropic nanostructures is foundational to many emerging technologies, such as energy storage devices, photonic elements, and sensors. Methods to rapidly (>mm/s) manufacture large area assemblies (≫cm2) with simultaneous control of thickness (<10 nm), nanoparticle spacing (<5 nm), surface roughness (<5 nm), and global and local orientational order are still lacking. Herein, we demonstrate such capability using flow-coating to fabricate robust, self-supporting mono- and bilayer fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The Stokes parameters were also analyzed to determine the purity, or degree of polarization, of the harmonic field. For pure light polarization states, either linear or circular, S 0 2 = S 1 2 + S 2 2 + S 3 2 , whereas mixed polarization states yield S 0 2 > S 1 2 + S 2 2 + S 3 2 . Hence, a nonzero difference between S 0 2 and the summation over the remaining Stokes parameters indicates the harmonic wave is a superposition of polarization states.…”
Section: Plasmon-resonant Excitation Selectively Amplifies Circularly...mentioning
confidence: 77%
See 2 more Smart Citations
“…The Stokes parameters were also analyzed to determine the purity, or degree of polarization, of the harmonic field. For pure light polarization states, either linear or circular, S 0 2 = S 1 2 + S 2 2 + S 3 2 , whereas mixed polarization states yield S 0 2 > S 1 2 + S 2 2 + S 3 2 . Hence, a nonzero difference between S 0 2 and the summation over the remaining Stokes parameters indicates the harmonic wave is a superposition of polarization states.…”
Section: Plasmon-resonant Excitation Selectively Amplifies Circularly...mentioning
confidence: 77%
“…Indeed, changes in metal–metal atom bond lengths on the subangstrom scale are known to induce large second-order responses in 2-D metals . Most commonly, gold nanorods are formed in solution by silver-ion-assisted, seed-mediated synthesis that utilizes cationic surfactants, such as cetyltrimethylammonium bromide (CTAB). Although this approach typically yields single-crystalline nanorods, the final structures are characterized by rounded or faceted tips and an overall asymmetric shape when viewed at the atomic level . Scanning transmission electron microscopy (STEM) images of several gold nanorods used in this study are shown in Figures A and S1A.…”
Section: Lattice Anisotropy Leads To Nonlinear Chiroptical Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AuNRs were prepared according to the scale up protocol. 2,3 The growth solution was prepared by mixing HAuCl 4 (500 µL, 0.1 M), AgNO 3 (500 µL, 0.1 M), CTAB (0.1g). Next, hydroquinone (1.25 ml, 0.1M) was added to the growth solution as a mild reducing agent.…”
Section: Synthesis Of Au Nrsmentioning
confidence: 99%
“…The appeal of PGNs stems from their tunability, where the design modularity of the nanoparticle core (size, geometry, and composition) and polymer canopy (graft density, composition, and molecular weight) prescribe their properties, processability, and interparticle potential. , As with stars and other architected macromolecules, PGNs bridge the gap between colloids and linear chains. , Due to the irreversibility of chain grafting and the range of composition, shape, and size, PGNs are expected to exhibit a rich array of phase behavior within the canopy, among nearest neighbors, as well as with respect to the shape of the assembly. For example, the polymer-grafted canopy has been shown to exhibit micro-phase separation in response to solvent and temperature. , Additionally, finite clusters of spherical PGNs exhibit directionally dependent interparticle potential due to the deformability of the grafted canopy .…”
Section: Introductionmentioning
confidence: 99%